2013
DOI: 10.2310/8000.2012.120914
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events are rare among adults 50 years of age and younger with flank pain when abdominal computed tomography is not clinically indicated according to the emergency physician

Abstract: Objective: Many emergency physicians (EPs) order ''confirmatory'' abdominal computed tomography (CT) in young flank pain patients, despite a high clinical suspicion of renal colic and the risk of radiation exposure. We measured the adverse outcome rate among flank pain patients identified as not requiring abdominal CT by the EP on a data form, regardless of whether CT was eventually ordered. Our secondary objective was to describe diagnoses other than renal colic identified by CT in this population. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Most patients who present to the ED with renal colic have few adverse events within a follow-up period of 180 days 1640. We chose to perform follow up at 30 days based on the recommended trial of medical expulsion therapy of 4–6 weeks 8,10,41,42.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients who present to the ED with renal colic have few adverse events within a follow-up period of 180 days 1640. We chose to perform follow up at 30 days based on the recommended trial of medical expulsion therapy of 4–6 weeks 8,10,41,42.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in a population of patients suspected of having appendicitis, a considerable number of children present with recurrent abdominal pain of other origins. These children could be exposed to CT radiation at every recurrent episode of abdominal pain if the use of CT were the protocol suggested for such clinical presentation [18,21,29]. Moreover, the cost of sonography is lower than that of CT. Transabdominal US has been performed as an imaging modality in patients with suspected appendicitis because sonography can rapidly help distinguish patients with appendicitis requiring computed tomography or surgery from those with a normal appendix.…”
Section: Discussionmentioning
confidence: 99%
“…Summary of current evidence A total of 21 publications addressed this question via different methods, including 8 retrospective studies, 7 prospective observational studies, 4 systematic reviews, and 2 RCTs (Table 2 in Supplement B). 2,6,12,15,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Only 1 study directly compared immediate CT to delayed CT in patients who were clinically improving in the EDand neither group had any alternative diagnoses considered lifethreatening. 28 "Alternative diagnoses" were not standardized and were not always clearly defined as dangerous, emergent, or urgent.…”
Section: 21mentioning
confidence: 99%
“…32,36 Of the studies, 2 defined young patients as those aged 18-50 years, and found no dangerous alternative diagnoses when clinicians suspected uncomplicated renal colic (95% CI 0-1.5% and 0-3%). 25,36 The range of 0%-9% reflects the heterogeneity of clinical contexts and patient characteristics: cohorts with older patients or less-strict inclusion criteria-such as in retrospective studies-had higher rates of dangerous alternative diagnoses.…”
Section: 21mentioning
confidence: 99%